Algorithm of blockchain data provenance based on ABE - Youliang TIAN; Kedi YANG; Zuan WANG; Tao FENG (Tongxin xuebao)
To solve the problem that the blockchain-based traceability algorithm mainly used homomorphic encryption and zero-knowledge proof for privacy protection,making it difficult to achieve dynamic sharing of traceability information,a blockchain data traceability algorithm based on attribute encryption was proposed.In order to realize the dynamic protection of transaction privacy,the strategy update algorithm applicable to block chain was designed based on the CP-ABE scheme proposed by Waters to achieve dynamic protection of transaction privacy.In order to realize the dynamic update of the visibility about block content,based on the strategy update algorithm,the block structure was designed to achieve the dynamic update about the content visibility of the block.The security and experimental simulation analysis show that the proposed algorithm can realize the dynamic sharing of traceability information while completing the protection transaction privacy.